SOIL QUALITY OF BHILWARA DISTRICT (RAJASTHAN) IN RELATION TO PISCICULTURE - RANA, R. S.; CHANDRAPRAKASH, CHANDRAPRAKASH (Journal of Indian Fisheries Association, 2015)
The .Present llaper deals with the llhysico-chemical data of 13 rainfed and drain able dry bundhs of Bhihvara district, Rajasthan (India). All the dry bundhs studied showed a slightly alkaline pH ranging from 7.5 to 8.5. Ek-ctrical conductivity ranged from 2 to 8 millimhos/cm. Organic carbon in sediment fluctuated from 0.30 to 0. 75%. Nitrogen, llhosphate and potassium levels Â·were fairly good, at 30 to 50 and 24 to 36 mg/100 g of soil res1lectively. Based on these data it was inferred that these dry bundhs were highly lli’Oductive and suitable for freshwater fish culture.